LOW FREQUENCY PASSIVE SEISMIC ANALYSIS FOR CHARACTERIZING HYDROCARBON PRESENCE IN THE KENDAL SUBBASIN - Maman Rohaman; Alfathony Krisnabudhi; Hasan Tri Atmojo; Ikhwannur Adha (Rudarsko-geološko-naftni Zbornik, 2025)
This study explores the characteristics of hydrocarbon presence in the Kendal subbasin, Central Java, using low-frequency passive seismic (LFPS) techniques as a direct hydrocarbon indicator. Waveform data were collected in 2024 using five deployed stations, including areas near oil wells, oil seeps, and non-seepage zones, to assess the presence of hydrocarbons trapped within fault-bounded anticlines. The thrust faults in the study area significantly influence the Kerek Formation, creating structural folds that serve as potential hydrocarbon traps. In analysing that potential trap system, the waveform data is processed following the time windowing and bandpass filtering to enhance signal clarity and isolate relevant seismic responses. This study identified significant Power Spectral Density (PSD) anomalies within the 1-4 Hz frequency range, which aligns with anomalies observed in Vertical-to-Horizontal Spectral Ratio (VHSR) data. The consistent occurrence of these anomalies in both PSD and VHSR data highlights the potential of LFPS as a reliable tool for detecting subsurface hydrocarbons in geologically complex regions like the Kendal subbasin. The polarity analysis was also performed, resulting in an average azimuth of 0.430 NNE, with an average dip of 0.680. These results inform us that the hydrocarbon flows from the border fault in the north to the well. This method complements the other geophysical method analysis to find new hydrocarbon opportunities.